Precise autonomous navigation of LEO constellations based on PPP-B2b signals and inter-satellite ranging measurements - Shi, Yali; Li, Min; Xu, Tianhe; He, Bei; Yang, Xuan; Wang, Dixing (GPS solutions, 2025)
Owing to their superior Earth observation capability and robust signal landing power, low Earth orbit (LEO) satellite constellations have various applications that include remote sensing, satellite communication, gravity field recovery, and navigation augmentation. Real-time (RT) positioning of such constellations is crucial because it offers precise location and attitude information for the diverse sensors onboard LEO satellites. Autonomous orbital determination is essential for LEO constellations because it alleviates the computational load on ground systems and eases the communication pressure of data transmission. It remains a substantial challenge to achieve high orbital accuracy (typically on the scale of decimeters) for LEO satellite navigation constellations required for reliable and accurate navigation by users relying on broadcast ephemeris. Currently, the RT corrections from the International Global Navigation Satellite System Service are accessible almost only via the internet. Fortunately, precise point positioning (PPP)-B2b corrections broadcast by geostationary orbit satellites represent a valuable reference for achieving high-accuracy RT precise orbit determination (POD). Moreover, large LEO constellations possess the capability for inter-satellite ranging. This study considered the case of the twin satellites of the gravity recovery and climate experiment-follow on formation-flying mission to verify autonomous POD performance. A 10-day experiment revealed that incorporating PPP-B2b corrections notably enhanced the along direction accuracy, and resulted in an average orbital determination accuracy of 0.11, 0.18, and 0.08 m in the radial, along, and cross directions, respectively. The constraint of inter-satellite ranging can substantially mitigate orbit deviations in LEO satellites attributable to observation interruptions. Even with 60-min data interruptions, the addition of inter-satellite ranging ensures that orbital accuracy remains at pre-interruption levels. The combination of PPP-B2b signals and inter-satellite ranging is instrumental both in achieving high-precision RT POD and in suppressing orbital deviations triggered by observation anomalies.